METHODOLOGICAL FOUNDATIONS FOR ASSESSING THE EFFICIENCY OF INSTITUTIONAL SUPPORT OF CLIMATE FINANCING (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In increasing the effectiveness of climate financing, an important place belongs to a perfect methodology for assessing the effectiveness of its institutional provision. The significance of its development and implementation is due to numerous problems in the field of climate financing. At the same time, the accurate measurement of the effectiveness of initiatives for financing climate initiatives / programs / projects remains a difficult task due to the complexity of the distinction between purely climate financing and general financial assistance to countries, the multiplicity of sources of climate financing, the problems of accurately reflecting its financial flows and the imperfect system of their accounting and reporting.The purpose of the article. The purpose is to determine the methodological foundations for assessing the efficiency of institutional support for climate financing.Methods. The study uses a systematic approach, monographic and historical methods, methods of comparative and expert analysis.Results. The significance of developing methodological principles of institutional provision of climate financing is determined. The following types of efficiency of institutional support for climate finance are identified and characterized in view of its polymorphic nature: economic, social, environmental, energy efficiency, commercial marketing; allocative, organizational, managerial, functional; efficiency of measures taken within the framework of international climate requirements; efficiency of distribution of funds between areas/subjects/objects of program financing; primary and multiplicative efficiency, absolute and comparative, intermediate and final, real and calculated, strategic and tactical, actual and forecasted, static and dynamic, synergistic. The blocks of a comprehensive assessment of the efficiency of institutional support for climate finance are presented. The problems of assessing the efficiency of climate finance and its institutional support are clarified. The criteria and indicators of assessing the efficiency of institutional support for climate finance are presented.Conclusions. The methodology for assessing the effectiveness of institutional support for climate finance should focus on identifying / analyzing / assessing key areas / areas of institutional regulation, which will enable coordination of efforts to harmonize approaches / interests in combating / combating / mitigating / adapting to climate change / restoring / transforming. This in turn requires a clear understanding of the consequences of climate change / sources and procedures for climate finance / climate and related financial risks; perfect disclosure and reporting related to climate change, international cooperation.
Keywords: climate finance, climate financing, methodology, institutional support, methodological principles for assessing the effectiveness of institutional support for climate finance.